Peran Guru PAI sebagai Arsitek Budaya Religius di SMK Muhammadiyah 03 Nogosari Boyolali - Hidayati Rina Setyawati; Joko Subando (TSAQOFAH, 2026)
Although the strengthening of religious culture in schools has been widely examined in Islamic education, discussions that specifically position Islamic Religious Education (PAI) teachers as architects of religious culture through the perspective of social construction still need to be strengthened. This study aims to analyze the role of PAI teachers as architects of religious culture and to explain the process of constructing religious culture through the stages of externalization, objectivation, and internalization at SMK Muhammadiyah 03 Nogosari Boyolali in the 2026/2027 Academic Year. This study used a qualitative approach with a library research method. Data sources were obtained from books, scientific journal articles, research findings, educational policy documents, and relevant literature on Islamic education, religious culture, and the social construction theory of Peter L. Berger and Thomas Luckmann. Data were collected through documentation and analyzed using content analysis techniques to identify, interpret, and synthesize concepts related to the research focus. The results of the study show that PAI teachers have a strategic role as role models, motivators, facilitators, guides, and social architects in building religious culture in schools. The process of constructing religious culture takes place through three stages, namely externalization through the inculcation of Islamic values in learning, role modeling, and religious habituation; objectivation through the institutionalization of religious values in school rules, programs, and traditions; and internalization through students’ appreciation of religious values until they shape their daily character and behavior. These findings confirm that the success of developing religious culture requires synergy among PAI teachers, school principals, students, parents, and the entire school community. The implications of this study provide theoretical contributions to the development of Islamic education studies and the social construction of school culture, as well as practical implications for educational institutions in strengthening the role of PAI teachers as the main drivers of an Islamic, humanistic, and sustainable educational environment.